Spatiotemporal differentiation and optimizing decision of the “agricultural production-farmer life-rural ecology” system in county villages (Journal of agricultural resources and environment, 2021)
为了因地施策促进乡村可持续发展，以山东省为例，构建县域乡村地域系统的农业生产、农民生活和农村生态的“三生”评价指标体系，运用空间分析技术和耦合模型开展县域乡村“三生”系统优化决策研究。结果表明：山东省县域乡村“三生”系统具有东北-西南地域分异特征，75.82%的县域乡村子系统处在磨合耦合阶段，乡村可持续性和协调性有待加强。乡村“三生”系统发展功能区具体分为低等协调持续发展区、中协调低持续发展区、低协调中持续发展区、中等协调持续发展区、高协调中持续发展区和高等协调持续发展区等六种类型，以中低协调发展区为主，占总量的72.6%。不同类型县域乡村“三生”系统功能区，应因地制宜、分类施策：鲁西南平原农区等低水平地区通过产业结构调整与转型，提高二三产业结构比例；胶东半岛等中等地区以产业集聚与技术创新为主，形成特色产业品牌；鲁北的高等协调地区以科学发展与示范建设为主，构建成熟乡村发展模式。乡村“三生”系统以耦合协调机理为依据，科学划分县域乡村发展功能区，对县域乡村振兴战略实施与乡村协调发展具有重要启示意义。 To implement local policies that promote rural sustainable development, this study constructed an evaluation index system for agricultural production-farmer life-rural ecologyin county villages, taking Shandong Province as an example, and analyzed the spatiotemporal characteristics of this rural system and the coupling coordination relationship between each subsystem using spatial analysis, an analytic hierarchy process, and a coupling model. The study also divided the development functional areas of the rural regional system in Shandong Province and suggested so